An Analysis of Black English Used In â€œThe Color Purpleâ€ Novel by Alice Walker - Zahrina Amelia; Fina Amalia Masri (ELITE: Journal of English Language and Literature, 2018)
Black English is a variety of English spoken by many African Americans. Most people consider that Black English as a badly spoken version of Standard English. Therefore, this is the reason why the syntactic feature of Black English important to analyze. The knowledge about the syntactic feature of Black English may results that people will understand and recognize Black English. This research is aimed at describing the syntactic feature of Black English that Alice Walker used in her novel and to find the most dominant feature which occurs in the novel. This research used the syntactic analysis based on Lisa J. Green’s perspective. Then, the data were analyzed using the descriptive qualitative method. The data were collected by downloading, reading, classifying, and coding the data then analyzed by presenting the collected data, describing the use of the syntactic feature, and making a conclusion. The results of this research are the researcherfound 10 syntactic features of Black English used in The Color Purple novel, they are; multiple negations, negative inversion, zero auxiliary, lack of subject-verb agreement, ain’t as negated auxiliary, lack of auxiliary in wh-question and yes-no question, existential it, aspectual be and lack of genetive-‘s.